Germany under the swastika
Continued by: Fascism (ZK 16069). - German ed.: Hakenkreuz über Deutschland (ZK 16067). - French ed.: Sous la croix gammée (ZK 53399). - Swedish ed.: Tyskland under hakkorset (ZK 53400). - Spanish ed.: Bajo la esvástica (ZK 53402).